Neuroendocrine Regulation of Anxiety: Beyond the Hypothalamic‐Pituitary‐Adrenal Axis. (July 2016) - Borrow, A. P.; Stranahan, A. M.; Suchecki, D.; Yunes, R.
Abstract : The central nervous system regulates and responds to endocrine signals, and this reciprocal relationship determines emotional processing and behavioural anxiety. Although the hypothalamic‐pituitary‐adrenal (HPA) axis remains the best‐characterised system for this relationship, other steroid and peptide hormones are increasingly recognised for their effects on anxiety‐like behaviour and reward. The present review examines recent developments related to the role of a number of different hormones in anxiety, including pregnane neurosteroids, gut peptides, neuropeptides and hormonal signals derived from fatty acids. Findings from both basic and clinical studies suggest that these alternative systems may complement or occlude stress‐induced changes in anxiety and anxiety‐like behaviour. By broadening the scope of mechanisms for depression and anxiety, it may be possible to develop novel strategies to attenuate stress‐related psychiatric conditions. The targets for these potential therapies, as discussed in this review, encompass multiple circuits and systems, including those outside of the HPA axis.